The effect of managerial creativity and innovative leadership towards school performance in UAE - Khalifa Alyousif Alsuwaidi, Khawla Ahmed (2021)
In today’s competitive era and changing atmosphere, managerial creativity and innovative leadership contributes towards the education system by overcoming the challenges of innovation. Creativity and innovation measures are needed to help accomplish goals while pushing the school managers to be more creative and critical with their decisions. Creativity is the talent to come out with new ideas by changing, reapplying or combining existing ideas. This study aims to identify the effect of managerial creativity and innovative leadership towards school performance in UAE. The data was collected using a standardized questionnaire with 5-points Likert Scale. A questionnaire survey was carried out amongst the employees of Abu Dhabi selected schools. A total of 260 questionnaires were collected of which 243 responses were found to be valid. Analysis of Moment Structures Equation Modelling (AMOS-SEM) model was developed based on 12 groups related to this study which are: managerial creativity; innovative leadership attributes; promotion of professional development; creating climate for creativity and change; managers encouragement of creativity; action orientated; confidence; emotional stability attributes; openness; risk tolerance; domain expertise and school performance. The findings of this study will encourage the school managers to be critical of their efforts and ideas which promotes a better overall school performance. The findings indicated that managerial creativity and innovative leadership towards school performance in UAE were supported during testing of the related hypothesis using structural modelling. The effect size of the sample groups on school's performance is medium from the R² (coefficient of determination). The most significant category is the managerial creativity group based on the path co-efficient values. The implication of this research is the implementation of these findings can enhance the managerial creativity and encourage innovative leadership in schools of Abu Dhabi, UAE. In turn, with a good education system it will help to promote the growth and the betterment of the nation.